Den'gi i politika . Den'gi i politika . Money and Politics . Деньги и политика - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The Visit of the U. S. Secretary of State, Warren Christopher, to Moscow; Russian-American trade relations; the extraordinary Session of the Heads of states and governments of the European Union; interview with the businessman Mikhail Bocharov, president of the International Russian Club, about Russian property abroad; segment on Geneva's banks; interview with William J. Holstein, chief editor of the weekly "Business Week"; segment on the work of the Center for International trade in Moscow. Contributors: Shal'nev, Aleksandr (Anchor) Визит в Москву Государственного секретаря СШA Уоррена Кристофера; российско-американские торговые отношения; чрезвычайная сессия глав государств и правительств Европейского Союза; беседа с предпринимателем Михаилом Бочаровым, президентом Международного Русского клуба, о российской собственности за рубежом; сюжет о женевских банках; беседа с Уильямом Холстином, главным редактором газеты "Business Week, сюжет о деятельности Центра международной торговли в Москве. Создатели: Шальнев, Александр (Ведущий/Ведущая)